Crucial Philosophical Implications of Neuroplasticity - Peluffo, Lucas (Journal of NeuroPhilosophy, 2024)
This article briefly reviews neuroplasticity’s basic terms and mechanisms and then emphasizes three crucial philosophical implications. (1) Considering the relationship of epistemology with the brain, the main organ of human intelligence is now proven to have the capacity to reorganize itself structurally. (2) Neuroplasticity has startled metaphysicians by embodying a mechanism that appears to challenge any strict—non-interactive—interpretations of the controversial term mind-body dualism. (3) Within morality and ethics, many neuroscientific studies performed on Buddhist meditators of Indic meditative traditions have linked positive neuroplasticity with empathy, compassion, and loving-kindness, indicating that these qualities can be developed consciously and suggesting that they may be intrinsic to human beings.